2019
DOI: 10.1111/1365-2745.13233
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of a non‐native invader erode native plant fitness in the forest understory

Abstract: The direct role of non‐native plant invaders in driving negative population‐ and community‐level processes of native species has been recently questioned. Addressing this controversy requires determining quantitatively if invaders negatively affect native population fitness. Because the invasion of non‐natives often coincides with other anthropogenic stressors, experiments that partition the putative impact of non‐natives from other known stressors and assess their potential synergies are required. While many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 62 publications
4
27
1
Order By: Relevance
“…Garlic mustard consistently has negative effects on native mycorrhizal plant species (e.g., Stinson et al 2006, Cipollini et al 2008, Wolfe et al 2008). These negative effects on mycorrhizal plant species are consistent with garlic mustard’s disruption of native mycorrhizal mutualisms, which leads to water stress and carbon stress (Brouwer et al 2015, Hale et al 2016) and decreases in vital rates (Brouwer et al 2015) and population growth rates (Bialic‐Murphy et al 2019). In addition, garlic mustard alters plant communities (Stinson et al 2007).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Garlic mustard consistently has negative effects on native mycorrhizal plant species (e.g., Stinson et al 2006, Cipollini et al 2008, Wolfe et al 2008). These negative effects on mycorrhizal plant species are consistent with garlic mustard’s disruption of native mycorrhizal mutualisms, which leads to water stress and carbon stress (Brouwer et al 2015, Hale et al 2016) and decreases in vital rates (Brouwer et al 2015) and population growth rates (Bialic‐Murphy et al 2019). In addition, garlic mustard alters plant communities (Stinson et al 2007).…”
Section: Discussionmentioning
confidence: 69%
“…Experimental evidence in both controlled and field settings has established that garlic mustard reduces native plant performance and population growth through the disruption of their mycorrhizal associations (e.g., Stinson et al 2006, Callaway et al 2008, Wolfe et al 2008, Barto et al 2011, Hale et al 2011, 2016, Brouwer et al 2015, Bialic‐Murphy et al 2019). Furthermore, garlic mustard is a poor direct competitor (Meekins and McCarthy 1999, Bossdorf et al 2004), and has no known direct phytotoxic effects (Brouwer et al 2015, Hale et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Arisaema is unpalatable and is rarely browsed by deer at our field sites (Heckel et al 2010). Modification in abiotic conditions and direct consumption of leaves, flowers, and fruits by overabundant deer reduce plant fitness of palatable herbaceous understory species (Knight 2004;Kalisz et al 2014;Bialic-Murphy et al 2019). Thus, we may expect that the negative effects of deer on the population dynamics of palatable species would result in competitive release of co-occurring unpalatable herbaceous species (Keane and Crawley 2002;Rooney and Waller 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work demonstrated that Alliaria can have cascading negative effects on the performance and population growth rate of AM dependent understory plant species 43 . We also previously found that Alliaria alters the diversity of native plant communities by reducing the abundance of mycorrhizal plant species, with no subsequent changes in non-mycorrhizal plant species 53 .…”
Section: Non-native Invadermentioning
confidence: 99%